Updates in the Clinical Development of Epacadostat and Other Indoleamine 2,3-Dioxygenase 1 Inhibitors (IDO1) for Human Cancers - Komiya, Takefumi; Huang, Chao H. (Frontiers in Oncology, 2018)
Recent application of immunotherapy in clinical oncology revolutionized our management of advanced human cancers. Check point inhibitors targeting CTLA4 and PD-1/PD-L1 axis are immunotherapeutic agents currently available to treat a variety of cancers. However, a novel therapeutic approach is needed to further improve patient outcome with these agents. Indoleamine 2,3-dioxygenase 1 (IDO1) is a rate-limiting enzyme in the metabolism of essential amino acid tryptophan in the peripheral tissue. IDO1 is overexpressed in human cancer cells and suppresses effector T cell function and promotes regulatory T cells (Tregs). Overexpression of IDO1 is associated with poor patient survival in several types of human cancer. These findings indicate that IDO1 is a promising target that can improve the treatment outcome in the field of Immuno-oncology. Several orally available IDO1 inhibitors including Epacadostat have entered human clinical trials over the last few years without a major safety concern. Although there is no objective response in single-agent trials, combination regimens with PD-1 inhibitors appear to exceed the activity of PD-1 inhibitors alone. Recent phase III ECHO 301 trial testing the combination of Epacadostat with Pembrolizumab in melanoma did not show superior outcome compared to Pembrolizumab alone. This lead to halting of other phase III trials using IDO1 inhibitors. In this minireview, we will discuss the recent clinical development of Epacadostat and other IDO1 inhibitors.